2017
DOI: 10.1002/jcla.22200
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between LIN28B gene potentially functional variants and Wilms tumor susceptibility in Chinese children

Abstract: In summary, these results indicated that the LIN28B gene rs314276 C>A polymorphism alone and three combined polymorphisms may be able to modify WT susceptibility in Southern Chinese children. Our findings call for further validation in large studies with different ethnicities involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The 145 cases in the study were individuals newly diagnosed with neuroblastoma from the Guangzhou Women and Children’s Medical Center 19, 20, 21, 22, 23, 35. All tumors were histopathologically confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The 145 cases in the study were individuals newly diagnosed with neuroblastoma from the Guangzhou Women and Children’s Medical Center 19, 20, 21, 22, 23, 35. All tumors were histopathologically confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the genetic variants are single nucleotide polymorphisms (SNPs). LIN28B polymorphisms were associated with Wilms tumor [22] and neuroblastoma [23] susceptibility in Chinese children. However, the relationship of LIN28B polymorphisms with hepatoblastoma susceptibility has not been investigated.…”
Section: Introductionmentioning
confidence: 95%
“…Our previous epidemiological study showed that the LIN28B polymorphisms may be able to modify Wilms tumour susceptibility in Chinese children . As LIN28A is quite similar to LIN28B in either structure or cellular function, it is biologically plausible that LIN28A polymorphisms may also predispose to Wilms tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we evaluated the association between the LIN28A polymorphisms and Our previous epidemiological study showed that the LIN28B polymorphisms may be able to modify Wilms tumour susceptibility in Chinese children. 15 As LIN28A is quite similar to LIN28B in either structure or cellular function, it is biologically plausible that LIN28A polymorphisms may also predispose to Wilms tumour. Our results indicated that rs3811463 CC/TC genotype and rs34787247 A allele confer an increased risk of Wilms tumour.…”
Section: Discussionmentioning
confidence: 99%